ADMINISTRATIVE SANCTIONS ON RIVER DESTRUCTION ACCORDING TO LAW NUMBER 32 OF 2009 (Study at the Environmental Management Agency for Tulang Bawang Regency) - SD.Fuji Lestari Hasibuan, Satrio Nur Hadi, Dina Haryati Sukardi, Tahura Malagano (NOMOI Law Review, 2020)
The need for clean water is increasing with the rapid population growth, however.Its availability has decreased due to environmental destruction or pollution, one of which is rivers.Damage or pollution to rivers is caused by domestic, industrial and agricultural activities.Damage or pollution to rivers will have a negative impact on health and cause imbalance in the river ecosystem.The problems raised are why administrative sanctions are used as an instrument in controlling river destruction in Tulang Bawang Regency, and what are the legal consequences of administrative sanctions on perpetrators of river destruction in Tulang Bawang Regency.The problem approach in this study is a normative approach, this study uses quantitative dataanalysis. The results of the research and discussion show that administrative sanctions are an instrument in river pollution due to restoration of conditions, repair of damage, or in other words aimed at actions committed by business actors or activities that pollute rivers, and are one of the efforts to enforce laws against activities related to licensing requirements, environmental quality standards, environmental management plans and so on through administrative sanctions, as well as enforcement of administrative sanctions aiming at actions that violate the law or do not meet the permitted requirements to stop or return to their original state,namely before the occurrence of pollution or destruction.to.Local government policies that do not take sides with the environment have in the occurrence of various natural disasters or events that continue to occur invariousregions, especially in Bawang BawangRegency.Keywords: Administrative Sanctions, Perpetrators, River Destruction.